Roughing, semi-finishing and finishing of laser surface modified nickel bonded NbC and WC inserts for grey cast iron (GCI) face-milling. (January 2020) - Genga, R.M.; Rokebrand, P.; Cornish, L.A.; Zeman, P.; Brajer, J.; Woydt, M.; van Vuuren, A. Janse; Polese, C.
Abstract: An attempt to improve the machining performance of NbC-Ni cutting inserts by rapid pulse electric current sintering (PECS), TiC and Mo2 C additions and laser surface modification (LSM) was done. Use of a nickel binder and additions TiC and Mo2 C to liquid phase sintered (LPS) NbC based samples led to comparable hardness (>13 GPa) and KIC ( 10 MPa.m 1/2 ) to LPS WC-Co/Ni samples. The laser surface modification (LSM) technique produced a 2.5 μm thick self-carbide coating, increasing the surface hardness of all the samples. Laser surface modification was done to improve abrasion and attrition wear resistance. Face-milling of grade 17 grey cast iron (BS 1452/GG35) was conducted at 100–500 m/min cutting speeds ( v c ) and 0.25–1.5 mm depths of cut (ap ). The insert wear was measured after every pass, and analyzed by annular dark field scanning transmission electron microscopy (ADF-STEM). During roughing, WC-Co based inserts had the lowest flank wear rate (FWR) values, with the WC-10Co (LPS) insert having a FWR of 10.15 μm/min after 20 min cutting time. However, during semi-finishing and finishing, NbC-4TiC-12Ni (PECS) and NbC-4Mo2 C-4TiC-12Ni (PECS) inserts had the lowest FWR values, showing up to six times longer tool life than the WC-Co (LPS) inserts based inserts and 12 times longer life than the WC-Ni based inserts. Generally, LSM improved the NbC inserts' tool life, reducing the FWR values in all NbC based inserts in all cutting tests. Highlights: All PECS samples had higher hardnessess and lower K1c than corresponding LPS samples, with the WC-10Co (PECS) sample having the highest hardness. The WC-10Co samples had better combination of hardness, K1c and TRS than the NbC samples. Additions of TiC and Mo2 C to NbC-12Ni and PECS significantly improved the properties. During roughing, the WC-Co inserts had the lowest FWR after a cutting time of 20 minutes, due to the high TRS and K1c . During semi-finishing and finishing, the NbC-4TiC-12Ni (PECS) and NbC-4TiC-4Mo2 C-12Ni (PECS) inserts had the lowest FWRs Generally, laser surface modification (LSM) reduced the FWR values for all the NbC based inserts.